DERADIKALISASI PENAFSIRAN AL-QURâ€™AN - Mohammad Zaenal Arifin (IAIN Kediri, 2015)
Tafsir is an attempt to understand the Qurâ€™an from all its aspects according to the human capacity. TheÂ products of tafsir certainly plays a significant role in determining how public will understand Islam. Therefore,Â a Qurâ€™anic interpretation should be built upon a noble goal, which is to provide an ontological view that theÂ Qurâ€™an is a â€œBook of Raá¸¥mahâ€ encouraging the people to create a tolerant and moderate society. This paper isÂ an attempt to break the chain that led to the emergence of reconstructing radical interpretation of the Qurâ€™an.Â It will first present a critique on those radical interpretations, and then reconstruct them within the frameworkÂ of the Qurâ€™anâ€™s á¹£Äliá¸¥ li kulli zamÄn wa makÄn.Keywords: Radikalisasi, Deradikalisasi, á¹£Äliá¸¥ li kulli zamÄn wa makÄn